Monitoring experts: insights from the introduction of video assistant referee (VAR) in elite football - Ulrike Holder; Thomas Ehrmann; Arne König (Journal of Business Economics, 2021)
Along with incentive schemes, another well-established way to align the interests of principals and agents and, consequently, to reduce and eliminate biases and errors is the practice of monitoring. Considering the monitoring of experts, we evaluate the introduction of the most recent monitoring technology in football, the virtual assistant referee (VAR). Focusing on the German Bundesliga and the Italian Serie A, we analyse whether VAR has changed referees' decision-making behaviour and, in particular, whether this led to changes in referees' well-documented preferential treatment of home teams. By doing so, we use the introduction of VAR as a natural experiment to examine whether VAR can help overcome inefficiencies in referees' decision-making and whether it exposes any inefficiencies in the referee selection system. Ex ante (in-)efficiency would imply that few (many) changes in referee decisions are seen after the VAR introduction. Our results suggest, generally, that VAR impacts referees' decision-making. We confirm current research and conclude that prior to the introduction of the VAR, the home team tends to be favoured with respect to awarded penalty kicks, red cards and the amount of added time in games containing either penalty kicks or red cards. However, because the home bias only partially decreased with the introduction of VAR, it seems that the bias emerges more as a result of the advantages of playing in one's local surroundings than of the referees' decisions. We further show that VAR interventions do not correlate with referees' experience levels. Overall, these modest findings and even non-existent differences indicate that home bias occurs for reasons other than referees, suggesting that the process for training, promoting, and selecting referees at the highest league works well. Finally, our findings suggest that the VAR implementation is aimed at purposes other than classic agent monitoring.
Keywords: L83; J44; Z20; 650; Monitoring; Elite football; Video assistant referee; Home bias; German Bundesliga; Italian Serie A